Embodied Instruction: An Exploration and Qualitative Comparison of Expression and Performance of Yoga Instruction - Reeves, Tegan; White, Crystal L. (Frontiers in Education, 2021)
Toward a contextualization of embodied learning at the close of a cartesian era, the current work explores instruction designed around uniting mind and body. Employing both grounded and comparative methodology, this qualitative case study used verbatim time-stamped transcriptions of iterative semi-structured in-depth interviews and participant observations. Thematic analysis, using a theoretical lens derived from a yoga literature review, was used to identify themes in both interviews and classes. Within the instructor interviews, expressed understanding of yoga instruction themes of energetic state, personality of instruction, inviting experience and student vulnerability were identified. Within the class observations, observed instruction themes of scoping, cadence, silence, and inviting practice were identified. Overlap in expressed understanding and observed instruction were found in each theme. An example of the expressed understanding of a thematic concept is inviting experience: “If someone comes in the very first time and the teacher is very invasive and says, "Do this, do this, do this." And the next pose the teachers is hovering over them, [that student] is not going to learn. [I] let people be really all over the place at the beginning as-long-as they are safe. [I] allow them that kind of freedom, initially.”. This was supported in the observed instruction; an example of this is: “We're going to play with [a posture]. … a foot might lift. Maybe both feet…maybe the legs straighten.”. The current study yields preliminary insight into embodied instruction strategies to support further curriculum development and research in a post-cartesian/post-mentalist capacity.